Influence of the molecular structure on the tribological properties of choline-based ionic liquids as water-based additives under current-carrying lubrication - Wang, Ruozheng; Sun, Chufeng; Yan, Xiaoyan; Guo, Tingting; Xiang, Wenjun; Yang, Zhaozhao; Yu, Qiangliang; Yu, Bo; Cai, Meirong; Zhou, Feng (Journal of molecular liquids, 2023)
[Display omitted] •Choline/fatty acid ionic liquids were synthesized.•These ILs has good antifriction and wear resistance under current-carrying lubrication.•The tribological performance of ILs with the same alkyl chain length are better when the number of double bonds is less.•The tribological properties of ILs were improved under electric field regulation. In this work, four types of choline/fatty acid ionic liquids were synthesised and used as water-based lubricant additives in an ethylene glycol system, and the tribological behaviours of the mixtures were investigated under the control of an applied electric field. Under current-carrying lubrication, the friction and wear resistances of the steel friction pair lubricated with the ionic liquid-added lubricant became more pronounced. As the number of double bonds in the fatty acid structure increases, the molecular compactness decreases, and the friction-reduction performance is affected. Mechanistic analyses indicated that the [Ch][SA] ionic liquid can strongly adsorb to the metal surface and form a tribochemical reaction film during the friction process, leading to excellent tribological properties.